2009
DOI: 10.4103/0974-2727.59698
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Lipids, Calcium and Magnesium in Women with Hypothyroidism and Cardiovascular Diseases

Abstract: Lipid abnormalities in hypothyroidism contribute to the disproportionate increase in cardiovascular risk. A possible relationship between serum level of magnesium (Mg) and calcium (Ca) and cardiovascular disease was recorded. In this work, the possible correlation between lipid profile components and serum cations Ca and Mg was investigated. Matched healthy women were evaluated in a cross-sectional study. All parameters were measured spectrophotometrically. The results showed a significant decrease (P < 0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…[34] On the other hand, study conducted by Laurant et al [53] revealed that blood pressure of rats fed Mg-deficient diet was significantly higher than those fed control diet [53]. Similar report was found by Jin et al [50] where systolic blood pressure of Mg-deficient diet fed rats was significantly high [51]. In our present investigation, the results revealed that high Mg diet (HFD + MgCO3 600mg) reduced Systolic Blood Pressure (SBP) to nearly normal (112mmHg).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…[34] On the other hand, study conducted by Laurant et al [53] revealed that blood pressure of rats fed Mg-deficient diet was significantly higher than those fed control diet [53]. Similar report was found by Jin et al [50] where systolic blood pressure of Mg-deficient diet fed rats was significantly high [51]. In our present investigation, the results revealed that high Mg diet (HFD + MgCO3 600mg) reduced Systolic Blood Pressure (SBP) to nearly normal (112mmHg).…”
Section: Discussionsupporting
confidence: 58%
“…Many experimental studies have been done on hyperlipidemic animals in previous years which reported that calcium could be the mediator of the development of atherosclerosis while magnesium suppressed the development of atherosclerotic lesions in terms of lipid deposition in the aortic walls and the velocity of contraction of ventricular myocardium [45][46][47][48]. However, based on previous evidences regarding the effect of magnesium and calcium on the development of atherosclerosis, research have been continued till recent years to enumerate their impact not only on the development of atherosclerosis but also their effect on other important organs like liver and kidney [21,34,[49][50][51][52] since both of these elements play significant roles in the maintenance of our health. The present study, thereby, emphasized in understanding the effect of combined dose regimen of magnesium and calcium in diet of atherogenic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on magnesium and thyroid function revealed that serum magnesium levels in patients with hyperthyroidism are decreased while those in patients with hypothyroidism are increased; this change might be related to thyroid hormones causing increased magnesium excretion in the urine 33 . However, subsequent studies have produced contrasting findings; animal model 34 and clinical studies 35 , 36 found hypothyroidism to be associated with decreased serum magnesium levels, and the role of thyroid hormones on the magnesium urinary excretion rate was mainly related to their effect on the degree of urinary concentration. There were no differences in the levels of urinary magnesium or creatinine levels in patients with varying thyroid functionality 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common reasons for exclusion were inappropriate data reporting (n=10), unavailable full texts (n=3), conducted on pregnant women (n=3), children (n=5), goiter (n=2) or hyperthyroid subjects (n=11), and inappropriate control group (n=8). Finally 25 case-control or cross-sectional studies included in the present meta-analysis [3,4,[11][12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. From these studies 11, 10, 9, 8, 6, 4 and 3 articles reported Mg [3,13,15,17,18,20,22,[28][29][30]34], Zn [4, 11-15, 20, 23, 27, 29], Se [4, 12, 13, 19-21, 24, 32, 33], Cu [4, 11-14, 20, 23, 29], Fe [4,11,20,25,26,28], Mn [4,...…”
Section: Literature Searchmentioning
confidence: 99%
“…Finally 25 case-control or cross-sectional studies included in the present meta-analysis [3,4,[11][12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. From these studies 11, 10, 9, 8, 6, 4 and 3 articles reported Mg [3,13,15,17,18,20,22,[28][29][30]34], Zn [4, 11-15, 20, 23, 27, 29], Se [4, 12, 13, 19-21, 24, 32, 33], Cu [4, 11-14, 20, 23, 29], Fe [4,11,20,25,26,28], Mn [4,[11][12][13] and Pb [4,…”
Section: Literature Searchmentioning
confidence: 99%